To Continue or to Quit: Investigating the Role of Affective and Cognitive Engagement on Female School Dropout - Zhaohui, Cai; Chebet, Yegon Maureen; Sampene, Agyemang Kwasi (Psychology in the schools, 2025)
ABSTRACT Female school dropout remains one of the pressing issues in many emerging regions, limiting societal progress and gender equity. This paper assesses the linkage between affective engagement, cognitive engagement, student academic performance and female school dropout (FSD), providing novel insights into the mechanisms underlying this essential educational issue. Envisioning the Self‐Determination theory (SDT), this study employs a robust structural equation model (SEM) to evaluate direct and mediation connections among key variables. A sample of 430 female students in Kenya was selected to provide data for achieving the objectives of this study. The outcome from the empirical analysis revealed that affective engagement and cognitive engagement strongly improve student academic performance and reduce FSD. In addition, student academic performance emerges as a crucial mediator, translating the benefits of engagement into seeable educational outcomes. The study included control variables to improve the discussion of this topic, and the result confirmed that parental educational level significantly affects FSD and student academic performance. The study's insight collaborates with the SDT, demonstrating the imperativeness of fulfilling the psychological needs for connectedness and student engagement in promoting sustained academic participation. This study advances theoretical understanding and provides actionable suggestions for students, teachers, policy‐makers, and educators to address the gendered issues of educational disengagement. Summary Strong academic performance turns engagement into real success for female students. Boosting academic performance makes engagement efforts lead to better school outcomes. Parental support and meeting girls' needs are vital to lower dropout rates.